Surgical reconstruction of an open medial malleolus fracture using a novel technique: a case report - Kow, Ren Yi; Yuen, Jin Chuan; Ahmad Alwi, Akmal Azim; Abbas, Muhammad Firdaus; Low, Chooi Leng (Lippincott Williams and Wilkins, 2019)
Case: A 17-year-old male sustained an open fracture of the right medial malleolus (MM) with significant bone and soft tissue loss following a motor-vehicle accident. Following serial wound debridement, his ankle was effectively reconstructed with MM antiglide plate stabilization, iliac autogenous bone graft, and a free radial forearm soft tissue flap.